Increased iron content in the heart of the Fmr1 knockout mouse - Talvio, Karo (Biometals, 2021)
Trace elements have important functions in several processes involved in cellular homeostasis and survival. Dysfunctional metal ion homeostasis can make an important impact on cellular defence mechanisms. We assessed the concentrations of 23 trace minerals in different tissues (brain, spleen, heart and liver) of Fmr1 knockout (KO) mice that display the main phenotype of Fragile X syndrome (FXS), an intellectual disability syndrome and the best-known monogenic model of autism spectrum disorder (ASD). Altogether, seven minerals—Cu, Fe, K, Mg, Mn, Na, and P—were above the detection limit with the analysis revealing increased iron content in the heart of Fmr1 KO mice. In addition, levels of iron were higher in the cerebellum of the transgenic mouse when compared to wild type controls. These results implicate a role for dysregulated iron homeostasis in FXS tissues and suggest that defective iron-related mechanisms contribute to increased tissue vulnerability in FXS. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s10534-021-00320-1.